Rock Physics Formula and RMS Stacking Velocity Calculation to Assist Acoustic Impedance Inversion that Constrain Well Data - Handoyo; Mochammad Puput Erlangga; Paul Young (Journal of Geoscience, Engineering, Environment, and Technology, 2020)
This research ilustrate the generation of acoustic impedance inversion in the absence of well log using stacking velocity input in Salawati Basin, Papua, Indonesia using data obtained from seismic lines and stacking velocity section. Initial acoustic impedance modelswere first before the inversion process and were created by spreading the value of well log data to the all seismic CDP. The calculated acoustic impedance logs from standard sonic and density logs were used to build the initial model of acoustic impedance.First, the stacking velocities was first interpolated on a grid that has the same size as the seismic data using by means of Polynomial algorithm. This was closely followed by the conversion of the stacking velocities to interval velocities using Dix’s equation. The matrix densities were estimated by simple rock physics approach i.e. Gardner’s equation as a velocity function. The initial model of acoustic impedance was calculated by multiplying the densities section and interval velocities section. The resulting initial model of acoustic impedance was inverted to obtain the best of acoustic impedance section based on reflectivity.